Assess the maturity of source rocks and their oil potential in greater Kirkuk and surrounding area - Al Ahmed, Ahmed Asker; Alameedy, Usama; Almomen, Ahmed; Al Behadili, Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The region of Kirkuk and its surrounding areas, including (Baba, Jambour, Qara Chuq, Qaiyarah, Demir Dagh, Bai Hassan, Taq Taq, Makhul, Gilabat as well as southern Mosul and the cities of Erbil and Sulymania, are known as one of the oldest discovered oil fields in northern Iraq. This area presents a significant opportunity for further organic geochemical analysis to describe maturation zones and estimate economically generated hydrocarbons with particular reference to the Sargelu formation, to enhance hydrocarbons productivity. To assess the potential of these oil fields, it is essential to perform correlation, comparisons, and geochemical analyses of the data collected from exploration wells in the surrounding area. This approach provides key information and evidence related to the source rock precursors, maturation indices, and other physical properties. The depth of samples in this study ranges from 5,125 ft (1,562 m) to 10,866 ft (3,312 m). Notably, about 20% of these samples demonstrate Total Organic Carbon (TOC) values higher than 4%, with Rock-Eval Hydrogen indices (HI) between 100 and 600, corresponding to Tmax values within the oil generative window. The proven TOC value that has been measured is 16%, while the recorded HI value is 442, and the Tmax value of 439°C. The oil and gas accumulations of the Cretaceous and Tertiary in the Mesopotamian Basin and Zagros fold belt are overlying mature Jurassic source rocks, emphasizing the importance of vertical migrat ion in hydrocarbon generation. Terpane and Sterane biomarker distributions as well as stable carbon isotope values were determined for oils in the region and potential Sargelu source rock extracts in order to determine dependable oil-to-source rock correlations. The remarkable API gravity, sulfur content, and biomarker ratio provide valuable insights into the source and maturity of various reservoirs. The high sulfur content and wide range of API gravity, from extra heavy to light, are achieved within the range of 8.5–43.3 API.